Accounting for Differences in Depression Stigma Between Canadian Asians and Europeans. (May 2015) - Shamblaw, Amanda L.; Botha, Francois B.; Dozois, David J. A.
Stigma is an important barrier to recovery from depression. Individuals of Asian origin show greater levels of depression stigma compared with individuals of European origin. This study examined the mediators of the relationship between ethnicity and depression stigma in a North American context. A sample of university students, including 199 Canadian Europeans and 249 Canadian Asians, completed a variety of measures through an online study. Stigma toward an individual with depression was measured using both the Depression Attribution Questionnaire-27 and a Social Distance Scale. The perception of social norms, the belief that depression brings shame to one's family, a social dominance orientation, and conservative values mediated the relationship between ethnicity and depression stigma with perceived norms and familial shame having the largest indirect effects. These findings are consistent with social identity theory and suggest avenues for anti-stigma interventions.